Tailoring American Architecture for Soviet Audience in 1965: “Modern architecture. U.S.A.” Exposition at Moma and ‘Arhitektura Ssha’ Traveling Exhibition (USSR) - Bass, Vadim G. (Actual Problems of Theory and History of Art, 2021)
The article examines Soviet-American architectural relations on the example of “Arhitektura SShA (Architecture of the USA)” exhibition, displayed in Leningrad, Moscow, and Minsk in 1965. The show played a critical role in familiarization of the Soviet public and builders with American architecture and making it fashionable in the USSR.‘Arhitektura SShA’ was a traveling exhibition, commissioned by USIA to Arthur Drexler, the curator of MoMA architectural department. At the same time, in May 1965, he launched an exhibition in MoMA entitled ‘Modern architecture. U.S.A.’The article is based on the materials from the MoMA archive, including documents (such as curator’s correspondence and draft programs) illustrating the process of preparation of the show, the selection of the exhibits, the work on the content, design and production.The main question of the research has been the following: what was the difference between the image of the American architecture proposed for the audience in the USSR and the USA? What edifices, building types, formal and stylistic tendencies did the curator focus on?
Keywords: architecture of the USA; architectural exhibition; MoMA; Soviet modernism; international context of Soviet architecture; American architecture in the USSR; Arthur Drexler; Louis Kahn